Socio-demographic determinants of the knowledge and attitude of Nepalese healthcare workers toward human monkeypox: a cross-sectional study - Das, Santa Kumar; Bhattarai, Abhinav; KC, Simran; Shah, Sangam; Paudel, Kiran; Timsina, Sakchhyam; Tharu, Sunraj; Rawal, Laba; Leon-Figueroa, Dawin A.; Rodriguez-Morales, Alfonso J.; Barboza, Joshuan J.; Sah, Ranjit (Frontiers in Public Health, 2023)
Human monkeypox is an infectious zoonotic disease and since May 2022, there has been a spike in cases worldwide. In this regard, a global health emergency has been declared by the World Health Organization (WHO) on July 23rd, 2022. Although there have been no confirmed human monkeypox cases in Nepal yet, the nation is undeniably at risk of an outbreak. Despite all preventive efforts and preparedness for monkeypox, there still remain several challenges including the literacy and knowledge of our healthcare workers regarding monkeypox. The aim of this study was to assess the level of knowledge and attitude of Nepalese healthcare workers regarding monkeypox. A cross-sectional study was performed on different healthcare workers at Tribhuvan University Teaching Hospital on the month of October 2022 using a set of validated questionnaires used previously in a Saudi Arabian study. An in-person survey was conducted where a total of 220 questionnaires were distributed. The response rate was 93%. Knowledge was categorized into high or low based on the mean knowledge score. The attitude was assessed using a 3-point Likert scale. The association of the knowledge and attitude of the respondents in accordance with their socio-demographics was statistically evaluated using Pearson’s Chi-square test. The mean knowledge score was 13. A larger proportion of the respondents (60.4%) demonstrated a high knowledge and 51.1% demonstrated a positive attitude. Studying monkeypox during medical education possessed a significant difference in the attitude (p = 0.025). Knowledge did not vary based on socio-demographic characteristics. Despite almost half a year into the monkeypox outbreak, Nepalese healthcare workers still have an unsatisfying degree of knowledge and a negative attitude regarding its control which shows the need for education and awareness.